The self-esteem REgime : an action plan for becoming the confident person you were meant to be - Burt, Clarissa; Krebs, Gary M. (Rowman & Littlefield, 2021)
"Despite years of progress, many women still suffer low self-esteem in various realms of life. Here, Clarissa Burt shares her program for building better self-esteem through a unique process that emphasizes awareness, poise, and assurance"--